Livestock Management Models Around Mt. Mutis Forest and Its Impact on Forest Sustainability - Rahman Kurniadi; Herry Purnomo; Nurheni Wijayanto; Asnath Maria Fuah (Jurnal Ilmu Kehutanan)
The study examined the financial feasibility and impacts of livestock management models found around Mt. Mutis forest in Timor Island of Indonesia. Data was collected through interviewing 40 communities around the forest. There were two livestock management models around the forest, the first model was livestock management which raise livestock in the cattle pen, and the second model was livestock management which graze livestock in the forest. This study found that both livestock management models were financially feasible. However, if commercial cost of workers was counted, the livestock management model which raise livestock in the cattle pen was financially not feasible while livestock management model which graze livestock in the forest was financially feasible. Livestock management model which graze livestock in the forest however had negative impacts on the regeneration of trees. On the basis of this study, it is suggested that the government should limit the forest area that could be used for forest grazing.